Numerical simulation of multiple hydraulic fracture propagation in heterogeneous coal reservoirs based on combined finite-discrete element method - Xia, Binwei; Zhang, Xingguo; Ma, Zikun; Xu, Xinqin (Frontiers in Earth Science, 2024)
Multi-stage fracturing in Horizontal well increases the permeability of coalbed methane by generating multiple fractures. However, the heterogeneity of coal reservoirs is a crucial factor that cannot be ignored in the study of multiple hydraulic fracture propagation. Therefore, we established a two-dimensional model for multiple hydraulic fracture propagation based on the combined finite-discrete element method (FDEM) and assigned a Weibull distribution function to the heterogeneity of the physical parameters of the cohesive elements in the model. The objective was to simulate and study the fracture propagation law of multi-cluster fracturing in horizontal wells in heterogeneous coal reservoirs. The research results indicated that: (1) as the heterogeneity of the coal reservoir weakened, the deflection angle of the main fracture increased. More secondary fractures were generated in the coal reservoir, leading to significant discontinuity. (2) The fracturing disturbance area was always concentrated at the tip of the main fracture, with a double wing shape.However, the fracturing disturbance areas at the tips of multiple main fractures could easily converge, with a square shape; (3) It is recommended to use a moderate injection rate and increase